Who consumes curative care expenditure of medical institutions in Beijing: a case study based on System of Health Accounts 2011 - Yan Jiang; Xiaowei Man; Xuefeng Shi; Liying Zhao; Wanjin Yang; Wei Cheng (BMC, 2023)
Abstract Background China's health system is challenged by complex health problems experienced by different population groups and caused by multiple diseases. This study examined the distribution of curative care expenditure (CCE) of medical institutions in Beijing using beneficiary characteristics such as residency, gender, age, and disease. Suggestions are presented for the development of health policies. Methods A total of 81 medical institutions with approximately 80 million patients in Beijing, China, were selected via a multistage stratified cluster random sampling approach. Based on this sample, the System of Health Accounts 2011 was used to estimate the CCE of medical institutions. Results The CCE of medical institutions in Beijing was ¥246.93 billion in 2019. The consumption of patients from other provinces was ¥60.04 billion, accounting for 24.13% of the total CCE. The CCE of female consumption (52.01%/¥128.42 billion) exceeded that of male consumption (47.99%/¥118.51 billion). Almost half of the CCE (45.62%/¥112.64 billion) was consumed by patients aged 60 or above. Adolescent patients up to an age of 14 (including those aged 14) mainly chose secondary or tertiary hospitals for treatment. Chronic non-communicable diseases accounted for the largest share of CCE consumption, with circulatory diseases accounting for the highest proportion. Conclusions This study identified significant differences in CCE consumption in Beijing according to region, gender, age, and disease. Currently, the utilization of resources in medical institutions is not reasonable, and the hierarchical medical system is not sufficiently effective. Therefore, the government needs to optimize the allocation of resources according to the needs of different groups and rationalize the institutional process and functions.